1998
DOI: 10.1089/lap.1998.8.47
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Disinfection with 2% Alkalinized Glutaraldehyde Solution for Reuse of Laparoscopic Disposable Plastic Trocars

Abstract: The reusability of disposable plastic trocars after high-level disinfection by alkalinized 2% glutaraldehyde solution was examined in a prospective study from the point of view of infection risk in order to determine the safety and economic benefits. For this purpose, 45 laparoscopic cholecystectomy cases were analyzed microbiologically and clinically. In 30 cases, trocars subjected to 15 min of disinfection by glutaraldehyde were used. In the remaining 15 cases, new trocars were used and a control group was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…Two studies did not report clinical outcomes, 310 and another did not include a clinical comparator. 6 A randomized controlled trial provides the highest level of evidence. A 2-arm prospective study provides higher quality estimates than a 2-arm study with 1 prospective and 1 retrospective arm (eg, before and/or after).…”
Section: R E S U L T Smentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies did not report clinical outcomes, 310 and another did not include a clinical comparator. 6 A randomized controlled trial provides the highest level of evidence. A 2-arm prospective study provides higher quality estimates than a 2-arm study with 1 prospective and 1 retrospective arm (eg, before and/or after).…”
Section: R E S U L T Smentioning
confidence: 99%
“…Variance analyses or sensitivity analyses should be conducted when there is uncertainty about the quality of the estimates. Gundogdu et al [4] Kozarek et al [5] Wilcox et al [6] Browne et al [7] Plante et al [8] Male et al [9] Nanta et al [10] Dirschland Smith [11] Type of device In Table 4, we summarize the total savings as a percentage of the cost of the device indicated by studies that considered only costs related to devices and reprocessing. Cost savings were calculated as the cost of using new devices for every time the device was used minus the actual cost of reusing devices (ie, the price paid for the devices and the reprocessing costs).…”
Section: R E S U L T Smentioning
confidence: 99%
“…Because disposable trocars are more complex than reusable ones, their cleaning and disinfection may be more difficult than for the other instruments. However, Gundogdu et al reported that only one bacterial growth developed in 45 cases when 2% glutaraldehyde was used for this purpose [10]. DesCoteaux et al reported a wound complication rate of 1.8% in 816 patients when DLI were reused.…”
Section: Discussionmentioning
confidence: 99%
“…DLI were reused after high-level disinfection by alkalinized 2% glutaraldehyde solution, as described previously [10]. The smooth surfaces of all reused instruments were mechanically cleaned by brush; if they had a canal, they were also cleaned by brush and pressurized hot water.…”
Section: Methodsmentioning
confidence: 99%
“…In these two dierent settings, endoscopic surgery developed quite similarly in terms of number and type of operations performed. Also, to achieve cost eectiveness, both institutions developed similar solutions-namely the choice of reusable instruments and glutaraldehyde sterilization [7,10], and the surgeon's continuous selection of simpler and less expensive techniques, which did not require disposable supplies such as stapling devices, meshes, and endoloops.…”
Section: Discussionmentioning
confidence: 99%